Dissolution Enhancement of Raltegravir by Hot Melt Extrusion Technique - S. Abdul Jabbar, Ahmed (Iraqi Journal of Pharmaceutical Sciences, 2018)
The objective of the study to develop an amorphous solid dispersion for poorly soluble raltegravir by hot melt extrusion (HME) technique. A novel solubility improving agent plasdone s630 was utilized. The HME raltegravir was formulated into tablet by direct compression method. The prepared tablets were assessed for all pre and post-compression parameters. The drug- excipients interaction was examined by FTIR and DSC. All formulas displayed complying with pharmacopoeial measures. The study reveals that formula prepared by utilizing drug and plasdone S630 at 1:1.5 proportion and span 20 at concentration about 30mg (trail-6) has given highest dissolution rate than contrasted with various formulas of raltegravir.Keywords: Hot melt extrusion, Raltegravir, Plasdone S630.